2014
DOI: 10.3390/jcm3030679
|View full text |Cite|
|
Sign up to set email alerts
|

Fetal Aneuploidy Detection by Cell-Free DNA Sequencing for Multiple Pregnancies and Quality Issues with Vanishing Twins

Abstract: Non-invasive prenatal testing (NIPT) by random massively parallel sequencing of maternal plasma DNA for multiple pregnancies is a promising new option for prenatal care since conventional non-invasive screening for fetal trisomies 21, 18 and 13 has limitations and invasive diagnostic methods bear a higher risk for procedure related fetal losses in the case of multiple gestations compared to singletons. In this study, in a retrospective blinded analysis of stored twin samples, all 16 samples have been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
121
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 20 publications
(23 reference statements)
2
121
0
1
Order By: Relevance
“…6 A prospective study of the accuracy of cell-free DNA testing noted 2 cases of discordant cell-free DNA test results for trisomy 21, which were associated with vanished twins. 11 The authors concluded that "(t)he gender of the living and apparently healthy fetus was confirmed to be female and thus, the cffDNA that caused the increased z-score for trisomy 21 can clearly be assigned to a deceased male fetus. "…”
Section: Discussionmentioning
confidence: 99%
“…6 A prospective study of the accuracy of cell-free DNA testing noted 2 cases of discordant cell-free DNA test results for trisomy 21, which were associated with vanished twins. 11 The authors concluded that "(t)he gender of the living and apparently healthy fetus was confirmed to be female and thus, the cffDNA that caused the increased z-score for trisomy 21 can clearly be assigned to a deceased male fetus. "…”
Section: Discussionmentioning
confidence: 99%
“…It is not advisable for low-risk population and multiple gestations at present, due to a small but definite risk of false positive. 5 In some cases, result may be uninterpretable (due to early gestation, maternal obesity leading to low fetal fraction or placental mosaicism). In such cases, diagnostic tests and ultrasound evaluation should be offered, although repeat sampling has also been considered.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several studies have shown that this phenomenon is a source of false positive cfDNA results, [13][14][15] whereby the contribution of additional cfDNA from the demised twin can be detected 8 weeks after the demise, creating an additional complement of fetal DNA. 13,14 The recent introduction of single-nucleotide polymorphism-based screening NIPT may provide a solution to this issue. 13 By scanning for the presence of polymorphic loci, this test can detect the presence of different fetal haplotypes, which can help confirm a previously undetected dizygotic vanishing twin when combined with morphology scan.…”
Section: Vanishing Twin Syndromementioning
confidence: 97%
“…13 Whenever a confirmed singleton pregnancy with additional haplotypes is noted on singlenucleotide polymorphism NIPT results, the patient should be counseled on proceeding with invasive diagnostic testing before definitive management. 14 …”
Section: Vanishing Twin Syndromementioning
confidence: 97%
See 1 more Smart Citation